Review of Coast and Marine Ecosystems in Temperate Australia Demonstrates a Wealth of Ecosystem Services - Gaylard, Sam; Waycott, Michelle; Lavery, Paul (Frontiers in Marine Science, 2020)
Temperate Australia has extensive and diverse coast and marine habitats throughout its inshore and offshore waters. The region includes the southernmost extent of mangroves, over 500 estuaries and coastal embayments, home to extensive meadows of seagrasses and tidal saltmarsh. In areas of hard substrate, rocky reefs are abundant and productive with large forests of macroalgae. Coastal regions can be densely populated by humans and often habitats can be degraded, polluted or lost, while some remain relatively isolated and pristine. These habitats provide services to society including provision of food, regulate our climate through sequestration of carbon, treating our waste and protecting our shorelines from damage from storms. Coastal areas are culturally importantly hubs for recreation and tourism. Habitat mapping demonstrates diverse habitats throughout temperate Australia, but a formal investigation of services provided by these habitats has been lacking. This review of ecosystem services provided by coast and marine environments throughout temperate Australia reveals vast and productive ecosystems that provide multiple ecosystem services, substantial value to the Australian economy and contribute to the health and well-being of people who live in, visit of benefit from services or products from these regions. Some of these are considered within traditional economic metrics such as provision of wild catch fisheries, but this review demonstrates that regulation and maintenance services including waste treatment and protecting shorelines from extreme events are under recognized, and their value is substantial. However, consistent with many locations globally, coast and marine habitats are under threat from increasing development, sewage, agricultural, industrial discharges, urban runoff and climate change. Resultantly, temperate Australian coast and marine habitat extent and condition is generally declining in many regions, putting the provision of services and benefits to the community at risk. Continued degraded or lost habitats indicate current management frameworks are not capturing the full risk from development and there are winners and losers in trade off decision making. Incorporating ecosystem services in decision making may allow an integrated approach to management, and acknowledgment of services provided could prevent habitats from being undervalued against economic and social interests, a practice that often results in environmental degradation.